Acinic Cell Carcinoma of the Parotid Gland with Four Morphological Features - David Rosero; Ramiro Alvarez; Paula Gambó; María Alastuey; Alberto Valero; Nerea Torrecilla; A. Belén Roche; Sara Simón (Iranian Society of Pathology, 2016)
Acinic cell carcinoma arising in salivary glands is a rare tumor, accounting for 2% to 5% of the primary neoplasms of the parotid gland. When these tumors are well-differentiated, the neoplasia has innocuous aspect, due to the similarity to normal parotid tissue. This makes the diagnosis difficult. Initially the malignancy of this tumor was uncertain; however, recent studies have declared it as malignant. The female / male ratio is 3:2. The nodule usually presents as solitary and well defined shape. Several authors have used different terms to describe histomorphological patterns of these tumors. Four descriptive categories (solid, microcystic, papillary-cystic and follicular) are useful for pathologists. Here we report a case of a 49 yr old man with a left parotid nodule of 5 cm. Parotidectomy was performed at the Hospital Universitario Miguel Servet, in Zaragoza (Spain). The microscopy showed a tumor with acinic semblance, having the four morphologic patterns previously described. The morphological and immunohistochemical study was consistent with the diagnosis of acinic cell carcinoma.